TATA LETAK BUKU TERJEMAHAN KOMUNIKASI INTERPERSONAL BERDASARKAN GAYA SELINGKUNG PENERBIT SALEMBA - Ariesti Putri Perdana; Noor Riyadhi (Jurnal Ilmiah Publipreneur, 2014)
Producing translation manuscripts has a different level of complexity of the local paper. Not only focusing on the content, the layout must also be observed more because it is crucial to the making of a book. The methods used to identify the problems and to get the solutions are a literary research, observation, and interview. Based on the results of discussion, there are several obstacles in layouting the translation book â€œKomunikasi Interpersonalâ€. How to deal with the obstacles is to pay more attention to the layout, the principles and elements due to the difference housestyles between the Cengage Publisher (source text) and Publisher Salemba (target text).